Pengaruh Harga dan Lokasi terhadap Keputusan Pembelian Konsumen (Studi pada Rocket Chicken Karangjati) - Aditya, Galuh; Ristanto, Hesti; Kusmanto, Kusmanto; Rubiyati, Rubiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2022)
The purpose of this study: 1). To determine the effect of price on purchasing decisions on Rocket Chicken Karangjati, 2). To determine the effect of location on cunsumer purchasing decisions on Rocket Karangjati. The population in this study was 96 respondents. The research was conducted by sampling with probability sampling technique. Obtained a sample of 96 data. The analytical technique used is multiple linear regression. The result of the study can be concluded that: 1). Price has a positive and significant effect on cunsumer purchasaing decisions, 2). Location has a positive and significant effect on cunsumer purchasing decisions.